2022
DOI: 10.1037/tra0001028
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the PTSD symptoms of polytraumatized youth during isolated phases of trauma-focused cognitive behavioral therapy.

Abstract: Objective: Gender differences in the development and severity of PTSD have long been observed, but much less is known about gender differences within the context of trauma-focused treatment. This study investigated gender differences in the PTSD symptoms of polytraumatized youth during Traumafocused Cognitive Behavioral Therapy (TF-CBT). Method: The sample included child welfare-involved youth ages 7-18 (N = 138) who experienced a mean of 4.78 types of trauma and received TF-CBT at a trauma treatment clinic. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
3
6
0
Order By: Relevance
“…More specifically, the quantitative results showed that trauma-related stress, especially hypervigilance and intense psychological distress were more prevalent in women than in men and more prevalent among married than single women. Posttraumatic response patterns among women and men with PTSD are consistent with other studies [ 52 , 53 ].…”
Section: Resultssupporting
confidence: 91%
“…More specifically, the quantitative results showed that trauma-related stress, especially hypervigilance and intense psychological distress were more prevalent in women than in men and more prevalent among married than single women. Posttraumatic response patterns among women and men with PTSD are consistent with other studies [ 52 , 53 ].…”
Section: Resultssupporting
confidence: 91%
“…Many studies (n = 8) explored the role that gender may have in the effectiveness of the treatment, with most studies (n = 7) underlining no significant differences and only one study (Spuij et al, 2015), underlining that boys improved less than girls, although only in secondary externalizing outcomes. These results are in line with the recent literature, according to which CBT is effective in reducing traumarelated symptoms, irrespective of gender (Ascienzo et al, 2022).…”
Section: Gendersupporting
confidence: 92%
“…Research into sex differences in PTSD has provided valuable insight into more efficient prevention and treatment strategies (Ascienzo, Sprang, & Royse, 2021 ; Olff, Langeland, Draijer, & Gersons, 2007 ), yet more gender- and sex-sensitive research and reporting is needed (e.g. see the gender policy of the European Association of Science Editors).…”
Section: Introductionmentioning
confidence: 99%